Implementasi Metode Pembelajaran Berbasis Masalah Pada Pembelajaran Tema 2 â€œSelalu Berhemat Energiâ€ Kelas IV Peserta Didik MIN 2 Kediri - Farah Diba (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
The background of this research is: to attract students in theme learning, there needs to be a fun learning method. Therefore, problem based learning methods is selected. Researchers chose the PBL because this approach uses a learning step by steps that define problems, diagnose problems, formulate alternative strategies, define and implement preferred strategies and evaluations. The focus of this research is: (1) Implementation of problem-based Learning method (problem-Based learn) in theme 2 Always save energy learners class IV D MIN 2 Kediri (2) supporting factors in implementing learning methods Problem-based Learning Methods (IVD MIN 2 Kediri Class). While the purpose of this research is: (1) to describe the implementation of problem-based learning method in theme 2